Similarity in parasite communities of the teleost fish Pinguipes brasilianus in the southwestern Atlantic: Infracommunities as a tool to detect geographical patterns - Timi, Juan Tomas (2010)
Patterns of distance decay in similarity among communities of the fish Pinguipes brasilianus (Teleostei: Pinguipedidae) from five areas in the southwestern Atlantic were investigated to determine whether the rate of decay varied depending on the community level or the parasite guild analyzed (ectoparasites, adult endoparasites and larval endoparasites). Similarities in species composition were computed at both the component community and infracommunity levels. Similarity indices were calculated between all possible pairs of assemblages from different zones. Infracommunity similarity values between and within host populations were averaged. Significance of linear regressions for similarity values against distance was assessed using randomization tests. Different patterns were observed for each guild, and similarity among infracommunities within host populations varied accordingly. Decay in similarity over distance was recorded for most communities. The slopes differed significantly between infracommunities and component communities in all cases, and stronger decay was always observed for infracommunities. Different geographical patterns in parasite communities were a consequence of variability in parasite availability in the different regions, modulated by oceanographic conditions, as well as variation among species in terms of host specificity and life-cycles strategies. Infracommunities showed a stronger effect of distance than component communities, probably due to the influence of short term and local variability of oceanographic conditions.